Economie del grottesco nell’opera letteraria di Balzac: Le cousin Pons (Itinera, 2013)
The essay focuses on relations between grotesque and melodrama in Balzac’s literary works. Unlike Victor Hugo, the grotesque takes up a specific function in the narrative and dramatic economy of Balzac’s novels. Le cousin Pons for example shows indeed the dialectical connection between melodrama and grotesque and the role of the reader, engaged in a critical task with reference to the characters, the structure and the emotional and moral values of the novel.